Effects of nitrite infusion on skeletal muscle vascular control during exercise in rats with chronic heart failure - Glean, Angela A. (Kansas State University, 2015)
Chronic heart failure (CHF) reduces nitric oxide (NO) bioavailability and impairs skeletal muscle vascular control during exercise. Reduction of nitrite (NO[subscript]2-) to NO may impact exercise-induced hyperemia particularly in muscles with pathologically-reduced O[subscript]2 delivery. We tested the hypothesis that NO[subscript]2- infusion would increase exercising skeletal muscle blood flow (BF) and vascular conductance (VC) in CHF rats with a preferential effect in muscles composed primarily of type IIb+IId/x fibers. CHF (coronary artery ligation) was induced in adult male, Sprague-Dawley rats. Following a >21 day recovery, mean arterial pressure (MAP, carotid artery catheter) and skeletal muscle BF (radiolabelled microspheres) were measured during treadmill exercise (20 m•min[superscript]-1, 5% incline) with and without NO[subscript]2- infusion. The myocardial infarct size (35 ± 3%) indicated moderate CHF. NO[subscript]2- infusion increased total hindlimb skeletal muscle VC (CHF: 0.85 ± 0.09, CHF+NO[subscript]2-: 0.93 ± 0.09 ml•min[superscript]-1•100g[superscript]-1•mmHg[superscript]-1, p<0.05) without changing MAP (CHF: 123 ± 4 mmHg, CHF+NO[subscript]2-: 120 ± 4 mmHg, p=0.17). Total hindlimb skeletal muscle BF was not significantly different (CHF: 102 ± 7, CHF+NO[subscript]2-: 109 ± 7 ml•min[superscript]-1•100g[superscript]-1, p>0.05). BF increased in 6 (~21%) and VC in 8 (~29%) of the 28 individual muscles and muscle parts. Muscles and muscle portions exhibiting greater BF and VC following NO[subscript]2- infusion were comprised of ≥63% type IIb+IId/x muscle fibers. These data demonstrate that NO[subscript]2- infusion can augment skeletal muscle vascular control during exercise in CHF rats. Given the targeted effects shown herein, a NO[subscript]2[superscript]--based therapy may provide an attractive “needs-based” approach for treatment of the vascular dysfunction in CHF.
Keywords: Heart failure; Nitrite; Exercise; Muscle; Blood flow; Nitric oxide; Kinesiology (0575); Medicine (0564); Physiology (0719)